Diagnosis of cerebral malaria: Tools to reduce Plasmodium falciparum associated mortality - Muppidi, Pranavi; Wright, Emily; Wassmer, Samuel C.; Gupta, Himanshu (Frontiers in Cellular and Infection Microbiology, 2023)
Cerebral malaria (CM) is a major cause of mortality in Plasmodium falciparum (Pf) infection and is associated with the sequestration of parasitised erythrocytes in the microvasculature of the host’s vital organs. Prompt diagnosis and treatment are key to a positive outcome in CM. However, current diagnostic tools remain inadequate to assess the degree of brain dysfunction associated with CM before the window for effective treatment closes. Several host and parasite factor-based biomarkers have been suggested as rapid diagnostic tools with potential for early CM diagnosis, however, no specific biomarker signature has been validated. Here, we provide an updated review on promising CM biomarker candidates and evaluate their applicability as point-of-care tools in malaria-endemic areas.